PEMIKIRAN ATEISME RICHARD DAWKINS:: STUDI KRITIS ARGUMENT FROM IMPROBABILITY GOD DELUSION - Achmad Fadel; Hasan Mujtaba (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2020)
History shows a constant debate between religionists and atheists. Armstrong wrote thatany new concept of divinity that emerged in society and rejected established traditionswould be labeled as atheist and marginalized. Today, one of the movements that are quitecriticized by religious people is New Atheism. He has a great influence in the westernworld. Richard Dawkins, as the founder, composed a special work entitled God Delusionas a response to the rejection of the supernatural and personal concept of God throughArgument from Improbability. He explained that the complexity of the universe is almostimpossible to come from a simple entity, namely God, but at the same time, a complexcreator also produces infinite regress. Therefore, he took the gradual evolution of the universe as an alternative explanation for the formation of nature. This article will interpretRichard Dawkins’ points of thought in God Delusion, and analyze them using the principlesof logic and philosophy. As a result, the author found several weaknesses in the argumentfrom improbability and the lens in viewing religion. First, the assumption of rejecting theargument of resentment is only to deny the supernatural concept of God. Second, the useof statistical probability arguments limited to natural laws does not lead to supernaturalconcepts. Third, complexity stems primarily from simplicity. Lastly, ignorance of the criteria for the existence of consequences for causes.